PENGARUH LATIHAN INTERVAL TRAINING TERHADAP DAYA TAHAN PEMAIN BOLA VOLI CLUB WAHANA PUTRA PEKANBARU - Ani, Rika Evi; Ramadi, Ramadi; Wijayanti, Ni Putu Nita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak : The problem raised in this research is "Training Interval Training on the Endurance of the Wahana Putra Pekanbaru Volley ball Player?" So that in the future athletes can perform and play much better and most importantly after research and find out if there is an increase in power hold the athlete in the game of volleyball in order to balance the opponent's game and achieve maximum results in the future. The form of this research is (using the one group pretest-posttest design approach) with the population of the Pekanbaru Wahana Putra Volleyball Club players. the data in this research are all populations of 8 people. The instrument carried out in this research was to use the Bleep Test, which aims to determine the effect of interval training exercises on the durability of the men's rides volleyball club pekanbaru. After that, the data was processed with statistics, to test normality using the lilifours test at a significant level of 0.05α. The hypothesis proposed is that there is an effect of the Interval Training exercise on the Endurance of Volleyball Players in Club Wahana Putra Pekanbaru. Based on the normal test analysis the data X produces Lhitung of 0.2188 and Ltable 0.285, meaning Lcount <Ltable. while the Y variable produces Lhitung of 0.1668 and Ltabel of 0.285. This means Lcount <LTable. Based on the analysis of statistical data, there is an average variable X 30 and the mean score of Y variable is 33.12, then the data is normally distributed. Thus, there is the effect of Interval Training exercises on the Endurance of Volleyball Players of Wahana Putra Pekanbaru club.Keywords: Interval training, endurance